In vitro Antibacterial Properties of Etlingera elatior Flower Extracts against Acne-Inducing Bacteria: Propionibacterium acnes and Staphylococcus aureus - D, Nurul Saidah; I, Salwani; AB, Mohd Hilmi; Z, Mohd Khairi; U, Rabiatul Adawiyah; S, Nurul ‘Adani (IIUM Medical Journal Malaysia, 2019)
Introduction: Acne is a common skin disorder and is generally caused by Propionibacterium acnes and Staphylococcus aureus. Etlingera elatior flower extract is known to have antibacterial properties however, the properties against these bacteria have not been extensively reported. Thus, this study aimed to investigate the antibacterial properties of the flower extract against these bacteria. Materials and Methods: The flower extract was subjected to sequential extraction using three different solvent polarities; n-Hexane, dichloromethane (DCM) and ethanol. The antibacterial properties were evaluated using the disc diffusion and broth dilution assays techniques by determining the inhibition zone diameter, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Total phenolic acids (TPC) and flavonoids contents (TFC) were estimated using Folin-Ciocalteu and aluminium-chloride colorimetric assay respectively. Morphological changes of the treated bacteria were studied using scanning electron microscope (SEM). Results: DCM flower extract showed the highest antibacterial properties against P. acnes; at 25 mg/ml it had the widest inhibition zone (11.39 ± 0.45 mm) and the lowest MIC (6.25 mg/ mL) and MBC (12.5 mg/mL). The ethanolic flower extract had the highest antibacterial properties against S. aureus; at 50 mg/ml the inhibition zone was 6.21 ± 0.25 mm and the MIC and MBC were both 12.5 mg/ mL. Ethanolic extracts had the highest TPC (966.304 ± 114.08 mg GAE/g) and TFC (796.33 ± 65.78 mg QE/ g). There was significant morphological changes of the treated bacteria observed under SEM. Conclusion: E. elatior flower extracts exhibited antibacterial properties against acne-inducing bacteria.